Use of rivaroxaban for the prevention of stroke in patients with nonvalvular atrial fibrillation in Spain. (May 2018) - Martí, Edelmira; Segado, Alejandra; Pastor-Galán, Irene; Amat, Paula; Remigia, Maria José; Solano, Carlos; Navarro, Blanca
Aim: To analyze the clinical profile and rates of stroke, major bleeding and intracranial hemorrhage of patients with atrial fibrillation (AF) treated with rivaroxaban in clinical practice.Methods: Retrospective study of AF patients anticoagulated with rivaroxaban in a Healthcare Area of Valencia, Spain. Patients started treatment with rivaroxaban from July 2012 to December 2015.Results: A total of 230 patients (mean age 76.9 ± 9.9 years; CHA2 DS2 -VASc 4.3 ± 1.7; HAS-BLED 1.7 ± 0.9) were included. Rates of stroke, major bleeding and intracranial bleeding were 0.4, 1.9 and 0.5 events per 100 patient-years, respectively.Conclusion: In this cohort of AF patients anticoagulated with rivaroxaban, despite patients being older and having a high thromboembolic risk, rates of stroke, major bleeding and intracranial bleeding were low.